Frequency of Occurrence of Pregnancy in Relation to Uterine Horn in Cattle in the Colombian Tropics - González Tous, Marco (Universidad de La Salle. Revistas. Revista de Medicina Veterinaria., 2014)
This paper aims to determine the frequency of occurrence of pregnancy in the right and left uterine horns of cattle in the Colombian tropics. Rectal palpation was performed in 1,534 cows to diagnose pregnancy and to indicate the pregnant horn (left or right). Additionally, 618 non-pregnant cows were examined to determine the presence of corpora lutea (CL) or follicle (F), and to identify the ovary (right or left) containing them. In pregnant cows, the percentages of right and left gestation were 63.1% (968/1534) and 36.9% (566/1534) (p ≤ 0.01), respectively, and in non-pregnant cows, 69 % of CL and 68% of F were found in the right ovary (p ≤ 0.01). Similarly, reproductive tracts of 300 pregnant cows were inspected, as well as those of 300 non-pregnant cows but with CL and F present. In pregnant tracts, the percentages of right and left gestation were 67.3% and 32.7% (p ≤ 0.01), respectively, and in non-pregnant cattle, 68% of CL and 65% of F were found in the right ovary (p ≤ 0.01). In conclusion, the highest percentage of pregnancies in cattle in the Colombian tropics is presented in the right horn; an increased presence of CL and F was also found in the right ovary.